Battlefield of the future 21st century warfare issues - Schneider, Barry R.; Grinter, Lawrence E.; Edited by Schneider, Barry R.; Grinter, Lawrence E. (Maxwell Air Force Base, Alabama Air University Press, 2001)
The authors of the essays in this book focus on issues relating to strategy and war fighting as the world moves into the twenty-first century. In these ten essays, the authors examine the debate over the future of airpower, the unique threat of biological warfare, the impact of the information revolution on warfare, and how changes in military technology might require a rethinking of the principles of warfare. These authors address whether new military technologies, new organization for warfare, and new strategies for employing forces on future battlefields will produce a revolution in military affairs.
Keywords: Military art and science--Forecasting -- Twenty-first century